2020
DOI: 10.1590/1980-57642020dn14-010002
|View full text |Cite
|
Sign up to set email alerts
|

Use of the movie “Lorenzo’s Oil” for didactic purposes in neuroscience and others health fields

Abstract: Although the traditional method of teaching is still the most popular nowadays, the use of different methodologies such as play approaches, for instance, could be used to make the teaching-learning process a more active approach. Nonetheless, the use of films that represent true stories are more pertinent in active teaching, especially those directly associated with a specific field and that are not merely dramatic. Lorenzo’s oil can inform students about many biological topics and problems linked to intensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…Compared to the previous studies our learners found some difficulty in following clips from Lorenzo`s Oil. 13,14 Possible reasons for this could be the language barrier/ the Italian accent present in this movie and relatively less well-known actors in this movie. Our study supports earlier findings that Cinemeducation helps to improve students' motivation to learn and improve learning of the Humanistic aspects of medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the previous studies our learners found some difficulty in following clips from Lorenzo`s Oil. 13,14 Possible reasons for this could be the language barrier/ the Italian accent present in this movie and relatively less well-known actors in this movie. Our study supports earlier findings that Cinemeducation helps to improve students' motivation to learn and improve learning of the Humanistic aspects of medicine.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Arguably the best movie where Biochemistry itself is the central character is “Lorenzo’s Oil”. 13,14 This movie can be an excellent tool for teaching Inborn Errors of Metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…First do not harm) проводили розбір понять «фармакорезистентна епілепсія», «епілептичний статус», традиційної і нетрадиційної протиепілептичної терапії [1,7,8], «Масло Лоренцо» (англ. Lorenzo's oil) -знайомство з орфанним захворюванням адренолейкодистрофією [16].…”
Section: реформування післядипломної медичної освітиunclassified
“…Awakenings) [11,12,18], тріолеат гліцерину і тріерукат гліцерину -«Масло Лоренцо» (англ. Lorenzo's oil) [16].…”
Section: реформування післядипломної медичної освітиunclassified